Organizing English Learner Instruction in New Immigrant Destinations: District Infrastructure and Subject-Specific School Practice - Hopkins, Megan; Lowenhaupt, Rebecca; Sweet, Tracy M. (American educational research journal, 2015)
In the context of shifting demographics and standards-based reform, school districts in new immigrant destinations are charged with designing infrastructures that support teaching and learning for English learners (ELs) in core academic subjects. This article uses qualitative data and social network analysis to examine how one district in the midwestern United States organized EL instruction. After describing the district's infrastructure for elementary EL education, we examine how this infrastructure supported teachers' work practice—the practices in which teachers engage with one another—as operationalized around instructional advice and information networks. Findings reveal that teachers' opportunities to learn about EL instruction varied significantly by the school subject and that these differences were directly related to the way in which the district built its EL educational infrastructure.